1988
DOI: 10.1136/jmg.25.4.227
|View full text |Cite
|
Sign up to set email alerts
|

A family showing apparent X linked inheritance of both anencephaly and spina bifida.

Abstract: A family is reported which includes five males, two with spina bifida, two sibs with anencephaly, and one with both high and low spinal lesions. The affected subjects came from four sibships in three generations. The mode of inheritance of these neural tube defects is consistent with X linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 14 publications
(1 reference statement)
0
18
0
3
Order By: Relevance
“…Thus it appears to be important for cell differentiation and cell proliferation and would be expected to be essential for all stages of growth and development. (Table 5) An example of an X-linked recessive disorder is the X-linked variety of anencephaly-spina bifida [ Jensson et al, 1988].…”
Section: Autosomal Recessive Traitsmentioning
confidence: 99%
“…Thus it appears to be important for cell differentiation and cell proliferation and would be expected to be essential for all stages of growth and development. (Table 5) An example of an X-linked recessive disorder is the X-linked variety of anencephaly-spina bifida [ Jensson et al, 1988].…”
Section: Autosomal Recessive Traitsmentioning
confidence: 99%
“…This has precluded the use of conventional genetic methods that are routinely employed for the elucidation of monogenic disorders. Fortunately, a few families have been reported that show a Mendelian, usually Xlinked, pattern of inheritance of NTD (Toriello et al 1980;Fellous et al 1982;Fineman et al 1982;Oman-Ganes and Shokeir 1984;Baraitser and Burn 1984;Toriello 1984;Jensson et al 1988).…”
Section: Introductionmentioning
confidence: 97%
“…Here, we report the analysis of an Icelandic family with apparently X-linked recessive inheritance of NTD (Jensson et al 1988). By employing exclusion mapping, haplotype analysis and multipoint linkage analysis, we have been able to exclude large regions of the X chromosome as the location for the responsible gene.…”
Section: Introductionmentioning
confidence: 98%
“…A incidência geral dos DTN oscila de 0,36 a 1,7 por mil nascimentos, com mortalidade neonatal em torno de 60% e seqüela em torno de 60% dos sobreviventes, sendo a mais grave a paralisia cerebral (Jensson et al, 1988;Källén et al, 1994;American College of Obstetricians and Gynecologists, 1996). Antecedente de abortamento espontâneo também parece aumentar o risco de DTN em gestações subseqüentes, especialmente para os casos de espinha bífida (Carmi et al, 1994).…”
Section: -Os Defeitos De Tubo Neuralunclassified
“…Park et al (1993) relatam um caso de feto masculino, cujo cariótipo apresenta excesso de 11 q distal e de 13 proximal, resultante de uma translocação familiar, associada à DTN . Fineman et al (1982) descrevem quatro famílias com herança autossômica dominante para disrafia espinhal e Jensson et al (1988) relatam uma família com provável padrão de herança ligada ao cromossomo X para anencefalia e espinha bífida.…”
Section: -Patogêneseunclassified